AN ANALYSIS OF TRANSLATION PROCEDURES OF DIALOGUES IN THE NOVEL “HARRY POTTER AND THE HALF-BLOOD PRINCE” - Rachel Rachel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2014)
The objective of the study are to find out what translation procedure and to find out which procedure is mostly applied in translating the dialogues in the Novel “Harry Potter and the Half-Blood Prince”. This research is a kind of literary research, where there writer used descriptive-qualitative method to analyze the novel. The writer selected 100 dialogues in the original novel “Harry Potter and the Half-Blood Prince” and the translated one “Harry Potter dan Pangeran Berdarah Campuran” to be analyzed the translation procedures used in translating those dialogues. The result of the data analyzed from the novel, showed that: (a) the translator used nine translation procedure which are based on Newmark’s theory of translation procedures. (b) the procedure that mostly applied in translating the dialogues in the Novel “Harry Potter and the Half-Blood Prince” is through-translation procedure. The total numbers of this classification are 28 items (28%). In line with the result, the writer concludes that through-translation procedure is often found in the Novel “Harry Potter and the Half-Blood Prince”. Basically, thhrough-translation procedure is the appropriate translation procedure since it is not reducing the meaning of the dialogue. This procedure is also holding out the stylistic and syntactical form of source language. The translator upheld the structure of the original text and did not change the meaning of the dialogue. The essence meaning of the text is transferred perfectly.